CITRA PEREMPUAN DALAM FILM HOME SWEET LOAN KARYA SABRINA ROCHELLE KALANGIE (KAJIAN FEMINISME) - Agus Wartiningsih; Anti; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2026)
This research aims to reveal the representation of women's self-image in the film Home Sweet Loan using a feminist theory approach. The development of a teaching module serves as a learning medium. This research uses a descriptive method with a qualitative research form. The source of this research is the film Home Sweet Loan. The theory used to address this research is feminist theory. The data collection technique uses a documentary study technique by selecting scenes from the research object. The results of this research reveal five aspects of women's self image: physical, psychological, family, social, and domestic. The findings include a total of 19 data points: physical self-image of women (7 data) is shown through attractive visuals and neat appearance; psychological self-image (12 data) is portrayed through resilience in facing conflicts and patience under pressure. The implementation of Indonesian language learning used in this research is the Teaching Module for Reviewing Fictional Works for Grade VIII, second semester of Junior High School (SMP) in the Merdeka Curriculum.